Failure to Rescue After Pancreatoduodenectomy: A Transatlantic Analysis. Issue 3 (September 2021) - Gleeson, Elizabeth M.; Pitt, Henry A.; Mackay, Tara. M.; Wellner, Ulrich F.; Williamsson, Caroline; Busch, Olivier R.; Koerkamp, Bas Groot; Keck, Tobias; van Santvoort, Hjalmar C.; Tingstedt, Bobby; Besselink, Marc G.
Abstract : Objective: This analysis aimed to compare failure to rescue (FTR) after pancreatoduodenectomy across the Atlantic. Summary Background Data: FTR, or mortality after development of a major complication, is a quality metric originally created to compare hospital results. FTR has been studied in North American and Northern European patients undergoing pancreatoduodenectomy (PD). However, a direct comparison of FTR after PD between North America and Northern Europe has not been performed. Methods: Patients who underwent PD in North America, the Netherlands, Sweden and Germany (GAPASURG dataset) were identified from their respective registries (2014–17). Patients who developed a major complication defined as Clavien-Dindo ≥3 or developed a grade B/C postoperative pancreatic fistula (POPF) were included. Preoperative, intraoperative, and postoperative variables were compared between patients with and without FTR. Variables significant on univariable analysis were entered into a logistic regression for FTR. Results: Major complications occurred in 6188 of 22, 983 patients (26.9%) after PD, and 504 (8.1%) patients had FTR. North American and Northern European patients with complications differed, and rates of FTR were lower in North America (5.4% vs 12%, P < 0.001). Fourteen factors from univariable analysis contributing to differences in patients who developed FTR were included in a logistic regression. On multivariable analysis, factors independently associated with FTR were age, American Society of Anesthesiology ≥3, Northern Europe, POPF, organ failure, life-threatening complication, nonradiologic intervention, and reoperation. Conclusions: Older patients with severe systemic diseases are more difficult to rescue. Failure to rescue is more common in Northern Europe than North America. In stable patients, management of complications by interventional radiology is preferred over reoperation. Abstract : Supplemental Digital Content is available in the text